FOSTERING CRITICAL THINKING SKILLS IN EFL UNIVERSITY STUDENTS DURING LISTENING COMPREHENSION USING DIGITAL TEACHING-MATERIALS: A CASE STUDY - Ma'fiyah, Imroatul; Riyani, Riyani; Annisa, Happy (University of Kuningan, 2023)
Understanding listening materials is perceived as the most challenging aspect of language learning by many EFL University students. They face difficulties in recognizing English words, phrases, pronunciation, vocabulary, and sentence complexity, compounded by the rapid speech rate of native speakers. Addressing these challenges, this study explores the use of digital materials that require students to analyse, evaluate and make informed judgments based on listening content, thereby nurturing higher order thinking skills. A qualitative case study was conducted, involving the collection of comprehensive data from course syllabi, lecturers and students. A total of sixty-one university students enrolled intermediate listening course, along with two listening lecturers, were actively engaged to enrich the data. The results shows that the use of digital materials, particularly the e-module, has proven to be effective. Students’ responses indicate that the e-module effectively facilitates critical thinking, improves reflective ability, and encourages motivation. Moreover, the e-module features, including well-defined learning outcomes, authentic materials, scaffolded learning activities, engaging multimedia elements, collaborative features, and opportunities for reflection and self-assessment, collectively contribute to foster critical thinking skills and motivation among students.